2021
DOI: 10.1097/ccm.0000000000004944
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anticoagulation Strategies in Patients Requiring Venovenous Extracorporeal Membrane Oxygenation: Heparin Versus Bivalirudin*

Abstract: OBJECTIVES: Extracorporeal membrane oxygenation is a life-sustaining therapy for severe respiratory failure. Extracorporeal membrane oxygenation circuits require systemic anticoagulation that creates a delicate balance between circuit-related thrombosis and bleeding-related complications. Although unfractionated heparin is most widely used anticoagulant, alternative agents such as bivalirudin have been used. We sought to compare extracorporeal membrane oxygenation circuit thrombosis and bleeding-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(154 citation statements)
references
References 21 publications
4
148
2
Order By: Relevance
“…Notably, transition from heparin to bivalirudin was accompanied by increase in survival rate (55% vs 31%, p=0.03) and reduced thrombocytopenia incidence in the bivalirudin group (69% vs 35%, p=0.003).Such results are in line with a recently published study on 295 VV ECMO patients, which documented higher 1 year survival rate, less circuit thrombotic events and decreased blood product administration in patients treated with bivalirudin compared to heparin [24]. Furthermore, it is our practice also to administer intravenous short-acting beta-blockers during VV ECMO treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Notably, transition from heparin to bivalirudin was accompanied by increase in survival rate (55% vs 31%, p=0.03) and reduced thrombocytopenia incidence in the bivalirudin group (69% vs 35%, p=0.003).Such results are in line with a recently published study on 295 VV ECMO patients, which documented higher 1 year survival rate, less circuit thrombotic events and decreased blood product administration in patients treated with bivalirudin compared to heparin [24]. Furthermore, it is our practice also to administer intravenous short-acting beta-blockers during VV ECMO treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Baseline PaO 2 /FiO 2 was 64 (52 -77):. Patients had high mortality risk according to risk scores: SOFA was 12 ± 5, SAPS II was 66 ± 25; APACHE II was 28 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), APACHE III was 103 ± 54 and the ECMOnet score 7 ± 4. Variations of pre ECMO respiratory parameters and cause of ARDS over the years under study are shown in supplementary figure 1 and 2, respectively.…”
Section: Study Populationmentioning
confidence: 99%
“…ELSO COVID-19 Interim Guidelines support implementing the standard ELSO anticoagulation guidelines in COVID-19 patients [ 62 ]. Systemic anticoagulation with bivalirudin on venovenous ECMO had lower circuit-related thrombotic events [ 63 ]. However, Parzy et al [ 64 ] reported that all their patients with SARS-CoV2 infection and ARDS, who were on venovenous ECMO, suffered from venous thromboembolism despite receiving the anticoagulation.…”
Section: Methodsmentioning
confidence: 99%
“… 49 Its use during ECMO has been successfully reported in the case of HIT. 51 Recently, Rivosecchi et al 52 performed a retrospective cohort study where they compared 162 patients receiving UFH with 133 patients receiving bivalirudin for anticoagulation on VV-ECMO. The bivalirudin group showed a decrease in clot formation in the ECMO circuit as well as a significant decrease in volume of blood product administration (red blood cells, plasma and platelet).…”
Section: Anticoagulationmentioning
confidence: 99%